Juvesenility = 소망 - Ch'ae Man-sik; 채만식, 1902-1950; Fulton, Bruce; Fulton, Ju-chan (서울 Asia Publishers(아시아), 2015)
"In "Juvesenility" the philistine first-person narrator reveals her snobbery and her ignorance of reality through her failure to understand her husband's eccentricity. ... Her husband's abnormal behavior derives from his creed that to survive in an upside-down world he too must act upside-down, a statement that carries overtones of ill health and distorted reality." --back cover.
한영대역본임. Texto paralelo en coreano e inglés con texto en inglés en páginas opuestas.
Keywords: Novela coreana